TRANSFORMASI STRATEGI PEMASARAN LEMBAGA PENDIDIKAN ISLAM MELALUI DIGITAL ADVERTISING: TINJAUAN TEORITIS DAN PRAKTIK - Nofitasari, Dian Evy; Hefniy; Fauzen, Muhamad (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
This study aims to examine the transformation of Islamic educational institutions' marketing strategies through digital advertising, with a focus on theoretical reviews and contemporary practices at MI Ihyauddiniyah. The research was conducted at MI Ihyauddiniyah, an elementary madrasah that is currently striving to develop a digital-based promotional strategy. The research approach is qualitative, employing data collection techniques such as in-depth interviews, participatory observation, and documentation. The findings reveal that digital advertising practices have begun to be implemented through social media platforms like WhatsApp, Instagram, and TikTok, but these efforts remain sporadic and unstructured. There is a gap between the institutional vision and the implementation of digital promotion, where the promotion strategy is not yet fully based on a solid theoretical framework and Islamic values that form the identity of the madrasah. The involvement of internal stakeholders is also not yet integrated into the digital promotion management system. The conclusion of this study emphasizes that the transformation of digital marketing strategies at MI Ihyauddiniyah shows a positive direction but requires strategic planning based on theory and Islamic values, strengthening promotion management, and enhancing human resource capacity. This study recommends the formation of a specialized digital marketing team and the development of systematic communication strategy guidelines to strengthen the madrasah's positioning in the digital era.